Analysis of Item Difficulty Level and Quality Distractor of English Questions - L, Syahrir; Sadapotto, Andi; Asrifan, Andi; Firman, Firman; Aksan, Muhammad; Putra, Benny (Universitas Muhammadiyah Gorontalo, 2024)
This research aims to analyze English questions at SMA Negeri 4 Sidrap with a focus on difficulty, type of questions, and cognitive level represented in the test. The research method used is content analysis, which involves collecting data in the form of an English question bank for class XI IPA 3 at SMA Negeri 4 Sidrap. The results of the analysis show that English questions at SMA Negeri 4 Sidrap tend to have varying levels of difficulty, with some questions being relatively easy and some questions being quite difficult. The most common type of question is multiple choice. The cognitive levels represented in these questions include basic understanding, application, analysis, and synthesis. Apart from that, this research also identified several aspects that need to be considered in preparing English questions at SMA Negeri 4 Sidrap, such as clarity of instructions, balance between various cognitive levels, and the use of language that is appropriate and easy to understand by students. It is hoped that this research will provide useful insights for English teachers at SMA Negeri 4 Sidrap in preparing questions that are more effective and varied, as well as helping to improve the quality of English teaching and learning at the school.